2016
DOI: 10.1007/s11999-015-4614-1
|View full text |Cite
|
Sign up to set email alerts
|

Open Surgical Treatment for Snapping Scapula Provides Durable Pain Relief, but so Does Nonsurgical Treatment

Abstract: Background Resection of the medial upper corner of the scapula is one option for treating patients with a painful chronic snapping scapula. However, the degree to which this procedure results in sustained relief of pain during long-term followup, and whether surgical treatment offers any compelling advantages over nonsurgical approaches at long-term followup, are not known. Questions/purposes We asked: (1) At long-term followup after surgical treatment of a painful snapping scapula, did patients' pain decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Nonoperative treatment of SSS can be as effective as surgical options for the majority of patients and underlying etiologies. 24 , 50 In this review, 4 studies (2 CSI and 2 ESWT therapy) found improved VAS scores from a mean of 7.7 ± 0.5 pretreatment to 2.4 ± 0.6 at the latest follow-up, which is comparable to the the 5 operative management studies reporting VAS improvement postoperatively, from a mean of 6.9 ± 0.7 to a mean of 1.9 ± 0.9. 1 , 2 , 7 , 8 , 13 , 23 , 35 , 41 , 47 Notably, this improvement in VAS is greater than the MCID of 3 for both groups.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Nonoperative treatment of SSS can be as effective as surgical options for the majority of patients and underlying etiologies. 24 , 50 In this review, 4 studies (2 CSI and 2 ESWT therapy) found improved VAS scores from a mean of 7.7 ± 0.5 pretreatment to 2.4 ± 0.6 at the latest follow-up, which is comparable to the the 5 operative management studies reporting VAS improvement postoperatively, from a mean of 6.9 ± 0.7 to a mean of 1.9 ± 0.9. 1 , 2 , 7 , 8 , 13 , 23 , 35 , 41 , 47 Notably, this improvement in VAS is greater than the MCID of 3 for both groups.…”
Section: Discussionsupporting
confidence: 57%
“…Finally, 1 study (24 patients, level 3 evidence) compared open superomedial scapular resection to nonoperative management for milder SSS presentations. 50 The authors concluded no significant difference between operative and nonoperative SSS management outcome in their series, with the operative group presenting with more pain at baseline. Because of the nonrandomized nature of this study and difference in symptom severity of the 2 groups preoperatively, it was cautioned that the study could not definitively conclude that nonoperative management is superior.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations